The Effect of Sugar Concentration and Drying Time to Nata De Coco Characteristic - Eka Lidiasari; Ina Permata Sari; Nindia Febianti; Boby Pranata (Universitas Muhammadiyah Semarang, 2026)
This study aimed to evaluate the effects of sugar concentration and drying time on the physical and chemical properties of nata de coco. A factorial completely randomized design with two factors sugar concentration (40%, 50%, and 60% w/v) and drying time (7, 8, and 9 hours) was used, with three replications per treatment. Physical parameters (texture, color, rehydration) and chemical parameters (moisture content, total sugar) were measured. Results showed that sugar concentration significantly affected color (L*), rehydration, moisture, and total sugar, while drying time significantly influenced texture, color (L*, a*), rehydration, moisture, and total sugar. The interaction between factors was not significant. The optimal condition was 40% sugar and 7-hour drying, producing 18.01% moisture, 64.67 °Brix total sugar, 117.0 gf texture, color values of L* = 63.0%, a* = 4.17%, b* = 10.93%, and 139.45% rehydration.